Motywacje i oczekiwania studentów I roku Uniwersytetu Śląskiego związane z podjęciem studiów teologicznych - Wójtowicz, Marek (Śląskie Studia Historyczno-Teologiczne, 2023)
The article shows the results of the inquiry researches of the 1st year theology students group. Picked up information concern the motivations and the expectations connected with beginning of theology study. Some personal details were analyzed too. Results were interpreted in relative to the whole group and in relative to three theological specialties – teacher’s, basic and priestly. Researches allowed to show profile of a typical theology student at the moment when he or she starts his or her studies.